2023
DOI: 10.3390/jpm13020244
|View full text |Cite
|
Sign up to set email alerts
|

High Concentration Hydrogen Mitigates Sepsis-Induced Acute Lung Injury in Mice by Alleviating Mitochondrial Fission and Dysfunction

Abstract: Background: Multiple organ failure (MOF) is the main cause of early death in septic shock. Lungs are among the organs that are affected in MOF, resulting in acute lung injury. A large number of inflammatory factors and stress injury in sepsis can lead to alterations in mitochondrial dynamics. Numerous studies have confirmed that hydrogen can alleviate sepsis in the animal model. The purpose of this experiment was to explore the therapeutic effect of high concentration (67%) hydrogen on acute lung injury in sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Notably, in such tumor cells, H 2 demonstrates a significant ability to activate the mtUPR response, likely attributed to the high basal and spare mitochondrial electron transport chain (ETC) activities of these types of tumor cells (Hasegawa et al, 2022). In addition, in terms of certain mitochondrial indicators, such as complex II activity and the expression of complex II, III and V, remain largely unchanged after hydrogen treatment in both the LPS-induced ALI (Fan et al, 2022) and septic mouse models (Dong et al, 2018;Xie et al, 2021;Zhao et al, 2023), which may be attributed to the fact that external stress did not significantly affect these indicators in the model group. In conclusion, H 2 has a significant mitigating effect on altered mitochondrial function caused by external stress.…”
Section: Effects Of H On Mitochondria Under Pathological and Normal C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in such tumor cells, H 2 demonstrates a significant ability to activate the mtUPR response, likely attributed to the high basal and spare mitochondrial electron transport chain (ETC) activities of these types of tumor cells (Hasegawa et al, 2022). In addition, in terms of certain mitochondrial indicators, such as complex II activity and the expression of complex II, III and V, remain largely unchanged after hydrogen treatment in both the LPS-induced ALI (Fan et al, 2022) and septic mouse models (Dong et al, 2018;Xie et al, 2021;Zhao et al, 2023), which may be attributed to the fact that external stress did not significantly affect these indicators in the model group. In conclusion, H 2 has a significant mitigating effect on altered mitochondrial function caused by external stress.…”
Section: Effects Of H On Mitochondria Under Pathological and Normal C...mentioning
confidence: 99%
“…The net balance between fission and fusion dynamically regulates the number and morphology of mitochondria (Chan, 2020). Previous studies have provided both in vivo and in vitro evidence that H 2 could alleviate lipopolysaccharide (LPS) or cecal ligation and puncture (CLP)-induced mitochondrial fission and promote mitochondrial fusion, evidenced by downregulation of Drp1 expression and upregulation of MFN1/2 or OPA1 expression (Dong et al, 2018;Lian et al, 2022;Zhang et al, 2023;Zhao et al, 2023). Lian et al showed that H 2 had a similar inhibitory effect to Mdivi-1, a mitochondrial fission blocker, on LPS-induced upregulation of Drp1 and its recruitment to mitochondria, which further confirmed the suppressing role of H 2 on LPS-induced mitochondrial fission (Lian et al, 2022).…”
Section: Regulation Of Mitochondrial Dynamicsmentioning
confidence: 99%
“…There is overwhelming evidence that mitochondrial dysfunction plays a vital role in the etiology of ALI [ 10 , 11 ]. Mitochondria are the site of oxidative metabolism in eukaryotes, which serve as scaffolds to initiate protein–protein signaling, and regulate Ca 2+ homeostasis and reactive oxygen species (ROS) [ 12 ]. Mitochondria are also involved in autophagy, mitophagy, cell death signaling, and innate immune responses [ 13 ].…”
Section: Introductionmentioning
confidence: 99%